Migraine Headache and Gender Differences of Bagdad City Population/ Iraq - Wael Waleed Mustafa1 , Samer Shukur Mohammed2, Zainab Ali Naser3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Migraine headache is a very common neurobiological disorder that is caused by increased excitabilityof the CNS. it has been increased the diagnosis of migraine headache which is based on the headache’scharacteristics and associated symptoms. It disturbs patients’ quality of life and weakens their work, socialactivities, and life quality. Recently WHO organization classified migraine headache as 19the along with allthe disabling diseases. Data on sex related differences in migraine headache more marked overlapping iwhtmigraine features in females’ subjects. We have conducted survey on gender difference and prevalence ofmigraine having the sample size of 500 patients from Iraq.We Selected Of 228 patients from 7-47 years who diagnosed with migraine headache according to BagdadGeneral hospital record from December 2018 to September 2019. After consent form signed, subjects wererequested to fill questionnaire included demographic, clinical characteristics, history of sickness, duration ofit, time happened in the months, general health, and other questionsThe primary outcome was women are more prone to migraine attacks than men. 2-4 hours of pain was themost common period of headache along with triggering factor of stress and poor sleep. Migraine headacheis s chronic daily sickness which is severe, and major health problem and disorder that effect on life quality.in summary, we would confirm that there is presence of distinct gender related differences in migraineheadaches add to some novel information that increase of level of migraine associated with family history.